Measuring the Quality of Dialogic Communication of Pesantren Al-Basyariyah Through Instagram - Mohammad Luthfi; Ryan Maulana Husen; Bambang Setyo Utomo; Tubagus Novalul Barokah (Jurnal Komunikasi, 2026)
public engagement through Instagram @albasyariyah_official referring to the theory of dialogic communication developed by Michael L. Kent and Maureen Taylor with five measurement indicators; the dialogic loop, the usefulness of information, the generation of return visits, the ease of interface, the rule of conservation of visitors. A quantitative approach with a descriptive survey method was used by taking a sample of 394 out of 25,098 population. The results of the study indicate that the quality of dialogic communication of Pesantren Al-Basyariyah through Instagram in the optimal category with total score of 53,863 in the range of Q2 - Q3. The ease of interface is the indicator with the highest score (80%), and the dialogic loop is the indicator with the lowest score (77%). Theoretically, the research results have implications for the development of dialogic communication theory in the context of social media. Practically, it contributes to improving dialogic communication in organizations, especially for pesantren, through digital media platforms